2015
DOI: 10.1155/2015/587465
|View full text |Cite
|
Sign up to set email alerts
|

APOEGene Polymorphism and Risk of Coronary Stenosis in Pakistani Population

Abstract: Genetic variation in lipid regulatory genes, particularly APOE, significantly influences the risk of coronary artery disease (CAD). This study aimed to assess the association between APOE polymorphism and angiographically assessed coronary stenosis in Pakistani population. A total of 695 subjects (22.3% female, mean age = 54 ± 11 years) presenting with chest pain were enrolled after obtaining written informed consent. CAD stenosis/extent was assessed by angiography. Patients were classified as having severe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…Only a small number of cases with mild/minimal coronary stenosis were available for comparison with severe coronary stenosis. Despite this limitation, we have previously reported a significant association of APOE with coronary stenosis in our sample [ 38 ] which has been confirmed by another study that also used an angiography-assessed small sample [ 36 ]. Recently, more than 160 loci have been implicated with CAD [ 4 , 39 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Only a small number of cases with mild/minimal coronary stenosis were available for comparison with severe coronary stenosis. Despite this limitation, we have previously reported a significant association of APOE with coronary stenosis in our sample [ 38 ] which has been confirmed by another study that also used an angiography-assessed small sample [ 36 ]. Recently, more than 160 loci have been implicated with CAD [ 4 , 39 ].…”
Section: Discussionsupporting
confidence: 74%
“…While one study examined 13 CAD risk SNPs in relation to premature CAD (mean age = ~40) assessed by angiography in a total sample of 650 [ 36 ], the other study screened 6 SNPs in 624 subjects where CAD cases were assessed only clinically (no angiography) and controls were apparently healthy subjects [ 37 ]. While no significant association was observed in the latter case-control study, 5 nominal significant associations were seen in the angiography-assessed premature CAD, including APOE , which we have also previously reported in our angiography-assessed sample [ 38 ]. Of the other 4 significant SNPs reported by Ansari et al [ 36 ], only one SNP ( MIA3 /rs17465367) overlapped with our SNPs and those of Shahid et al [ 37 ], which was not significant in both studies.…”
Section: Discussionsupporting
confidence: 66%
“…APOE genotyping was completed by the same laboratory for both the PITT-ADRC and MYHAT study participants using TaqMan SNP genotyping assays, as described previously [28].…”
Section: Methodsmentioning
confidence: 99%
“…Another meta-analysis including 14 studies showed that subjects with ε 4 allele were associated with 26% increased risk of CHD compared with ε 3 allele [13]. Since the publication of these two meta-analyses, numerous studies have appeared in recent years [1417]. However, differences in study design, end point validation, choice of subjects, and limited statistical power have led to different results of Apo E genotypes on CHD risk in the general population.…”
Section: Introductionmentioning
confidence: 99%